2021
DOI: 10.1016/j.intimp.2021.107916
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the beneficial effects of high-dose interferon beta 1-a, compared to low-dose interferon beta 1-a in severe COVID-19: The COVIFERON II randomized controlled trial

Abstract: Introduction Coronavirus disease 2019 (COVID-19) has been a serious obstacle in front of public health. Interferon-beta 1a (IFN-β 1a) has been used to treat patients with COVID-19. We aimed to compare the effectiveness of high-dose IFN-β 1a compared to low dose IFN-β 1a in severe COVID-19 cases. Methods In this randomized, controlled, and clinical trial, eligible patients with confirmed SARS-CoV-2 infections were randomly assigned to receive one of the two following the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…Of these 24 studies, 16 were excluded as they were either nonclinical or non-randomised studies. The remaining eight studies [ 10 , 16 22 ] were included in qualitative synthesis (systematic review), but one study [ 22 ] was excluded from meta-analysis as it used IFN in experimental as well as in the control arm. All seven of the remaining articles were included in the meta-analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these 24 studies, 16 were excluded as they were either nonclinical or non-randomised studies. The remaining eight studies [ 10 , 16 22 ] were included in qualitative synthesis (systematic review), but one study [ 22 ] was excluded from meta-analysis as it used IFN in experimental as well as in the control arm. All seven of the remaining articles were included in the meta-analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…IFN-β, a subtype of type I IFN, has been investigated widely as one of the treatment options for COVID-19 as a repurposed drug [ 11 , 16 22 ]. The present piece of work is a systematic review and meta-analysis of the randomised controlled trials evaluating the efficacy of IFN-β in terms of mortality, LOHS and time to clinical improvement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Peiffer et.al conducted a small trial and reported that COVID-19 patients who received Nebulised (interferon) IFN-β 1a had significantly greater odds of clinical improvement [1116]. Higher or lower doses of IFN-β 1a in moderate to severe COVID-19 patients didn't show any improvement in terms of reducing mortality [1117]. Monk et.al in their trial administered Nebulized (interferon) IFN-β 1a.…”
Section: A Ifn-β 1a In Covid-19 Patientsmentioning
confidence: 99%